Hubungan Kompetensi, Komitmen Organisasi dan Kualitas Audit di Kantor Akuntan Publik Daerah Istimewa Yogyakarta - Erawati, Teguh; Sinaga, Benget Sardo (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to examine the effect of independence, competence, organizational commitment on audit quality. The sample used in this research is an auditor who works in a public accounting firm (KAP). This research uses a quantitative method with primary data as the source of data, and the sample obtained is 40 respondents. Respondents were taken using a porposive sampling technique. The research results show that competency has a positive effect on audit quality, organizational commitment has a positive effect on audit quality.